The Effect of Immobilization Stress on Learning and Spatial Memory and the Protective Role of Physical Activity in Male Rats - Nafiseh Afshari; Shahzad Tahmasebi Boroujeni; Naser Naghdi; Rasool Hemayat Talab (University of Tehran, 2014)
Increased level of stress has negative effects on cognitive functions. Thus, it is necessary to identify appropriate strategies to prevent cognitive and motor performance decline. The aim of this research was to study the effect of immobilization stress on learning and memory and the protective role of physical activity in them. From male Albino-Wistar rats of Pastor Institute, 32 rats were randomly divided into four groups. According to the type of the groups, rats were exposed to stress interventions including immobilization (two hours per day for 21 days), moderate running (30 minutes per day for 21 days), combination of stress interventions and running and also without any interventions. In order to determine the effectiveness of stress, animal weights were measured in two phases: before the protocol and after the tests. Morris Water Maze in several steps (four days for the acquisition phase, the fifth day for Probe test, three days for resting and the ninth day for recall test) was used for learning and testing of rats. ANOVA test with repeated measures and paired sample t test in acquisition phase and Tukey post hoc test were used to analyze data. The results revealed that stress damaged learning and memory (P=0.03). However, physical activity neutralized performance damage caused by stress (P=0.000). Physical activity group showed a significant positive effect on the time to reach the platform in the acquisition phase (P=0.005) and on cognitive function in recall phase (P=0.006) which was a sign of positive effect of physical activity on learning and memory. Therefore according to the present results which show that stress impairs learning and memory, it is expected that physical activity will be used as an effective factor to moderate stress.